2010
DOI: 10.1007/s10562-010-0318-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Cobalt Silicate and CoOx Cluster Anchored to SBA-15: Highly Efficient for Cyclohexane Partial Oxidation

Abstract: The present investigation showed that the surface cobalt silicate and CoO x cluster anchored to SBA-15 are highly efficient heterogeneous catalysts for the cyclohexane partial oxidation with air-like O 2 (20%)-N 2 (80%) mixture as oxidant in the continuously stirred tank reactor at 413 K and 1.0 MPa. Typically, selectivity of 84.6% at cyclohexane conversion of 14.5% can be achieved in a period of 2 h reaction. The performance of Co-catalyst is affected by the nature of Co species introduced to SBA-15. The surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Recently, interest has emerged in the catalytic properties of cobalt and cobalt-containing oxides. Cobalt oxides have shown activity for a wide range of reactions, including oxygen reduction in fuel cells and solar cells, , NO reduction, methane combustion, partial oxidation of hydrocarbons, low temperature, selective CO oxidation, ethanol steam reforming, and the water gas shift reaction . Many of these reactions typically require precious metals, making Co oxides attractive even if they may not be the optimal catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, interest has emerged in the catalytic properties of cobalt and cobalt-containing oxides. Cobalt oxides have shown activity for a wide range of reactions, including oxygen reduction in fuel cells and solar cells, , NO reduction, methane combustion, partial oxidation of hydrocarbons, low temperature, selective CO oxidation, ethanol steam reforming, and the water gas shift reaction . Many of these reactions typically require precious metals, making Co oxides attractive even if they may not be the optimal catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to synthesis of metal loaded mesoporous molecular sieves by direct synthesis and impregnation methods [3][4][5]. However, it is very difficult to introduce metal ions into SBA-16 by direct hydrothermal synthesis due to the difficulty in the formation of metal-O-Si bonds under the strong acidic conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…The problem may be that a different pH range was expected for the formation of ordered structure (pH ( 1) and for the introduction of metal species (pH [ 1) in one-pot hydrothermal synthesis [2]. Evaporation induced self-assembly (EISA) strategy has been successfully applied to the synthesis of ordered mesoporous silica materials (SBA-15, SBA-16) and various mesoporous metal oxides (TiO 2 , ZrO 2 , Al 2 O 3 , WO 3 and SnO 2 ) utilizing triblock copolymer as the template [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Overall selectivity to KA oil was 95% in a solvent free environment at 160°C and 1.0 MPa O 2 pressure in 6 h . Li et al also reported on Co/SBA‐15 where cobalt silicate was seen on the surface and cobalt oxide was anchored in the pores of SBA‐15. Collective effect of cobalt forms resulted in 14% conversion with 85% selectivity.…”
Section: Introductionmentioning
confidence: 89%